2016
DOI: 10.5433/1679-0359.2016v37n4supl1p2375
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of Tambaqui broodstocks in the state of Rondônia, Brazil: implications on production and conservation

Abstract: In recent years, the genetic monitoring of broodstocks in fish farming has been greatly highlighted due to its importance in the management and improvement of their production and conservation. Current study evaluates the genetic diversity of four Tambaqui broodstocks (Colossoma macropomum) in the state of Rondônia (Brazil) and discusses activities towards the species´s correct production management and conservation. Nine primers were employed to analyze 94 specimens from four fish farms in the municipalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
8
1
4
Order By: Relevance
“…The results acquired for most of the breeding centres analysed in the present study contrast with those obtained in studies of the C. macropomum stocks of a number of different Brazilian farms using RAPD and ISSR (Lopes et al, 2009;Jacometo et al, 2010;Lopera-Barrero et al, 2015 e;Ribeiro et al, 2016), which revealed high levels of genetic variability. Similar results have been obtained for some populations using microsatellites (Santos et al, 2016) and…”
Section: Genetic Differentiation Among Populationscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results acquired for most of the breeding centres analysed in the present study contrast with those obtained in studies of the C. macropomum stocks of a number of different Brazilian farms using RAPD and ISSR (Lopes et al, 2009;Jacometo et al, 2010;Lopera-Barrero et al, 2015 e;Ribeiro et al, 2016), which revealed high levels of genetic variability. Similar results have been obtained for some populations using microsatellites (Santos et al, 2016) and…”
Section: Genetic Differentiation Among Populationscontrasting
confidence: 99%
“…This reflects a number of sampling problems, such as the regional focus of many studies, the use of markers with a poor resolution, and the inadequate or indirect sampling of the broodstocks through the analysis of the fry. In addition, the studies often overlook important aspects of the captive environment, such as reproductive patterns, the effective population size of the farmed stocks, the risks of inbreeding depression, the potential for genetic improvement based on the existing broodstock, the differences in comparison with natural populations, and the associated chances of hybridization with these populations (Aguiar et al., ; Calcagnotto & Toledo‐filho, ; Gomes et al., ; Jacometo et al., ; Lopera‐Barrero et al., ; Lopes et al., ; Queiroz et al., ; Ribeiro et al., ; Santos et al., ; dos Santos et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A manutenção da variabilidade genética é um aspecto fundamental nesse processo, uma vez que a maioria dos programas de repovoamento utiliza peixes de cativeiro, os quais são normalmente sustentados por muitas gerações (González-Wangüemert et al, 2012). Dessa forma, faz-se necessário o monitoramento tanto dos reprodutores utilizados na produção dos estoques quanto dos indivíduos que serão soltos nos rios, para garantir a variabilidade genética deles e evitar efeitos na ictiofauna devido à deriva genética e consequente diminuição da capacidade de adaptação ao novo ambiente (Rodriguez-Rodriguez et al, 2010;Lopera-Barrero et al, 2016;Ribeiro et al, 2016).…”
Section: Introductionunclassified
“…Consequently, genetic studies are greatly relevant to monitor the species since they may be the basis of conservation and production programs (RIBEIRO et al, 2016). Microsatellite markers are currently widely used for assessment since they provide a great amount of information due to high polymorphism and their co-dominant characteristics (ABDUL-MUNEER, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%